Validation of the Patient Driven Payment Model (PDPM) in China - Xu, Yue; Zhi, Mengjia; Shao, Ningjun; Hu, Linlin (BMC health services research, 2025)
Background Post-acute care is rapidly developing in China; yet, a payment method for post-acute care has not been established. The Patient Driven Payment Model (PDPM) is a new case-mix system developed in the United States of America for classification of skilled nursing facility patients. This study aimed to examine the validity of an adapted version of PDPM for classifying post-acute care patients in China. Methods First, 13,496 post-acute care patients in seven facilities of Jinhua City from January 2018 to December 2020 were sampled and assigned to PDPM groups according to their clinical characteristics, functional status, and special care needs. Then, the effectiveness of grouping was analyzed by the percentage of variance in resource use explained by the classification (R 2 ), the reduction in variance (RIV), the class-specific coefficients of variation (CVs), and the weighted means for each group (case-mix indexes, CMIs). Results Under the adapted version of PDPM, each patient is classified into a group for each of the four case-mix adjusted components: (1) physical therapy and occupational therapy (PT&OT), (2) speech-language pathology (SLP), (3) nursing, and (4) non-therapy ancillary (NTA). Each component utilizes different criteria for classification. The adapted PDPM explained 11.1%, 6.1%, 14.0%, and 10.6% of the variance in PT&OT, SLP, nursing, and NTA cost per day, respectively, for the sample patients (all p < 0.001), which were similar to the results in the United States of America. The CV achieved good homogeneity in 10 PT&OT groups (CV: 0.17–0.69), 12 nursing groups (CV: 0.09–0.66), and 6 NTA groups (CV: 0.38–0.64). The CMIs of groups spanned a 9-fold range in PT&OT (CMI: 0.22–1.96), 11-fold range in nursing (CMI: 0.59–6.33), and 4-fold range in NTA (CMI: 0.72–2.91). Conclusions Our findings provide preliminary evidence that the PDPM is a reliable and valid case-mix system for classifying post-acute care patients in China, which could inform future payment policy for post-acute care in China.